MISOGYNISMS IN CHO NAM-JOO'S 'KIM JI-YEONG, LAHIR TAHUN 1982' NOVEL: FEMINISM LITERARY STUDY (MISOGINISME DALAM NOVEL 'KIM JI-YEONG, LAHIR TAHUN 1982' KARYA CHO NAM-JOO: KAJIAN FEMINISME SASTRA) - Rina Husnaini Febriyanti; Zuriyati Zuriyati; Saifur Rohman (Leksema: Jurnal Bahasa dan Sastra, 2020)
A woman deserves to get respect and equal position with a man in the feminist view. This study aimed to find out misogynism in the novel Kim Ji-yeong, Lahir Tahun 1982, written by Cho Nam-joo. The method was qualitative. The collected data was from words, phrases, clauses, and sentences, whether directly or indirectly stated by women characters in the novel affected by misogyny. Data analysis based on Bogdan & Biklen model (2007) was categorized and coded; afterward, it was interpreted and displayed descriptively. The result revealed three situations described they were misogyny in the domestic area, society, and institution. This study implies in the feminist perspective that it is crucial to avoid or prevent misogynism in lives.